Diarrhea During COVID-19 Infection: Pathogenesis, Epidemiology, Prevention, and Management - D'Amico, Ferdinando; Baumgart, Daniel C; Danese, Silvio; Peyrin-Biroulet, Laurent (Clinical gastroenterology and hepatology, 2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2/COVID-19) pandemic is a worldwide emergency. An increasing number of diarrhea cases is reported. Here we investigate the epidemiology, clinical presentation, molecular mechanisms, management, and prevention of SARS-CoV-2 associated diarrhea. We searched on PubMed, EMBASE, and Web of Science up to March 2020 to identify studies documenting diarrhea and mechanism of intestinal inflammation in patients with confirmed diagnosis of SARS-CoV-2 infection. Clinical studies show an incidence rate of diarrhea ranging from 2% to 50% of cases. It may precede or trail respiratory symptoms. A pooled analysis revealed an overall percentage of diarrhea onset of 10.4%. SARS-CoV uses the angiotensin-converting enzyme 2 (ACE2) and the serine protease TMPRSS2 for S protein priming. ACE2 and TMPRSS2 are not only expressed in lung, but also in the small intestinal epithelia. ACE2 is expressed furthermore in the upper esophagus, liver, and colon. SARS-CoV-2 binding affinity to ACE2 is significantly higher (10-20 times) compared with SARS-CoV. Several reports indicate viral RNA shedding in stool detectable longer time period than in nasopharyngeal swabs. Current treatment is supportive, but several options appear promising and are the subject of investigation. Diarrhea is a frequent presenting symptom in patients infected with SARS-CoV-2. Increasing evidence indicates possible fecal oral transmission, indicating the need for a rapid and effective modification of the screening and diagnostic algorithms. The optimal methods to prevent, manage, and treat diarrhea in COVID-19 infected patients are subjects of intensive research.